2010
DOI: 10.1029/2010ja015324
|View full text |Cite
|
Sign up to set email alerts
|

Zonal drift of plasma particles inside equatorial plasma bubbles and its relation to the zonal drift of the bubble structure

Abstract: [1] It has been observed that the zonal drift velocity of equatorial plasma bubbles is generally eastward. However, it has not been well understood whether the zonal drift of plasma bubbles is the same as the ambient plasma drift and what process causes differences in the drift velocities of the ambient plasma and bubbles. In this study we analyze the ion drift velocities measured by the Defense Meteorological Satellites Program and ROCSAT-1 satellites and the electric fields measured by the Communications/ Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 36 publications
(67 reference statements)
12
79
0
Order By: Relevance
“…Thus, those irregularities generated further to the west of Shenzhen are causing more scintillation on the GPS signals than those irregularities that drifted eastward toward midnight. Huang et al (2010) showed evidence that the eastward drift velocity of the irregularities is faster than that of the ambient plasma drifts when the bubbles are tilted westward. Muella et al (2014) revealed that the scintillations are more likely to be observed in the west sector of the sky above Sao Luis, a station located close to the geomagnetic dip equator.…”
Section: Spatial Distribution Of Scintillationsmentioning
confidence: 96%
“…Thus, those irregularities generated further to the west of Shenzhen are causing more scintillation on the GPS signals than those irregularities that drifted eastward toward midnight. Huang et al (2010) showed evidence that the eastward drift velocity of the irregularities is faster than that of the ambient plasma drifts when the bubbles are tilted westward. Muella et al (2014) revealed that the scintillations are more likely to be observed in the west sector of the sky above Sao Luis, a station located close to the geomagnetic dip equator.…”
Section: Spatial Distribution Of Scintillationsmentioning
confidence: 96%
“…Equatorial plasma bubbles result from the nonlinear evolution of the Rayleigh-Taylor instability. A unique feature of plasma bubbles is the existence of large upward ion drift caused by polarization electric field inside the depletion region (e.g., [43]). In order to show this feature, we plot the ion density and ion vertical velocity in The very large upward ion velocity is the plasma E × B drift caused by the polarization electric field and is the evidence that the plasma depletions are bubbles.…”
Section: Observationsmentioning
confidence: 99%
“…The zonal plasma drift speeds of equatorial nighttime plasma depletions observed using the imager aboard a highapogee IMAGE satellite during March-May 2002 had a strong longitudinal dependence and are maximum over the Indian sector (Immel et al, 2004). Martinis et al (2003) presented studies of plasma drift using OI 630.0 nm measurements from South American Sector.…”
Section: Introductionmentioning
confidence: 99%
“…Strong equatorial spread F (ESF)/EPBs typically arise soon after the PRE of the zonal electric field (Heelis et al, 1974;Fejer et al, 1999). Huang (2010) reported that more EPBs, expected during the main phase of magnetic storm, are generated more rapidly under stronger southward interplanetary magnetic field (IMF) conditions. However, all of these relate to the same physical process commonly believed to be associated with the RayleighTaylor (RT) instability (e.g., Kelley, 1989).…”
Section: Introductionmentioning
confidence: 99%